Development of Self-Funded Water Supply for People of Sidomulyo, Sragen Using Deep Well with Submersible Pump - Agus Ulinuha; Umar Hasan; Wijianto Wijianto (Universitas Muhammadiyah Surakarta, 2020)
The availability of water is a problem for the people of Sidomulyo, Krikilan, Sragen at dry season. Having a higher altitude than other areas causes the water from the government water supply company difficult, reaching the area, particularly at the peak time. Some people using water from bore water also have the same problem of limited water. It is, therefore, necessary to bore the deep well for getting enough water to satisfy the people’s needs. The deep level of the well should be enough to assure not to absorb the water source of people’s well. In this program, the well with the deep of 81 m is bored, and PVC water pipes are placed inside the hole assuring only the deep bore water is taken out. This is aimed to avoid taking water from the low-level source, which may reduce the water going to the people’s well. For pumping purposes, the submersible electric pump is used. It is 3 hp, 2500-Watt pump with a capacity of 18 m3 per hour. From the 3-day pumping test, the capacity of well is very enough to provide water needs for the 34 families of Sidomulyo. High-water storage with the dimension of (2.4 x 2.4 x 2) m3 has been constructed with a height of 7.4 m to the tank base. The power source is currently from the electrical utility but is planned will be from Solar Photovoltaic. From a financial perspective, the revenue from the water bill will support community activities.